2001
DOI: 10.2494/photopolymer.14.91
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Characterization of Pulsed Inductively Coupled Plasmas for Deposition of Thin Polyethylene Glycol-like Polymer Films.

Abstract: In this work we characterize pulsed inductively coupled rf plasmas of two organic precursor molecules, isopropyl alcohol and 1,4 dioxane using Langmuir probes and in-situ mass spectrometry.We identify the key ionized species diffusing to the substrate and offer an explanation as to how they are generated. We also analyze the deposited films using X-ray Photoelectron Spectroscopy and suggest a correlation between the measured plasma ion mass distributions and chemical bonding character of the deposit. The ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The present results indicate plasma conditions that could emphasize such molecular ions, which, as noted above, may be useful for identifying key ionized species diffusing to the substrate as well as mechanisms for ionization in the plasma. Indeed, it has recently been proposed that ion-molecule reactions in some plasma systems are vital for producing species that are critical to formation of particular film chemistries [10,11,53]. Specifically, Shamamian et al have found that an ion-molecule protonation reaction in isopropyl alcohol plasmas leads to formation of the fragment CH 3 CHCH 3 ϩ (m/z ϭ 43), whereas a direct electron dissociation-ionization reaction yields the CH 3 CHOH ϩ fragment ion (m/z ϭ 45) [11].…”
Section: Mass Spectrometry Of Fluorocarbon Plasmasmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results indicate plasma conditions that could emphasize such molecular ions, which, as noted above, may be useful for identifying key ionized species diffusing to the substrate as well as mechanisms for ionization in the plasma. Indeed, it has recently been proposed that ion-molecule reactions in some plasma systems are vital for producing species that are critical to formation of particular film chemistries [10,11,53]. Specifically, Shamamian et al have found that an ion-molecule protonation reaction in isopropyl alcohol plasmas leads to formation of the fragment CH 3 CHCH 3 ϩ (m/z ϭ 43), whereas a direct electron dissociation-ionization reaction yields the CH 3 CHOH ϩ fragment ion (m/z ϭ 45) [11].…”
Section: Mass Spectrometry Of Fluorocarbon Plasmasmentioning
confidence: 99%
“…Indeed, it has recently been proposed that ion-molecule reactions in some plasma systems are vital for producing species that are critical to formation of particular film chemistries [10,11,53]. Specifically, Shamamian et al have found that an ion-molecule protonation reaction in isopropyl alcohol plasmas leads to formation of the fragment CH 3 CHCH 3 ϩ (m/z ϭ 43), whereas a direct electron dissociation-ionization reaction yields the CH 3 CHOH ϩ fragment ion (m/z ϭ 45) [11]. By controlling the plasma parameters, the 45/43 ratio can be varied between 0.5 and ϳ2.8.…”
Section: Mass Spectrometry Of Fluorocarbon Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…We have earlier successfully used , mass-spectroscopic (MS)-electron impact fragmentation as a representation of plasma-electron induced fragmentation. We have shown that the positive-ion composition in the mass spectra of a particular molecule subject to impact fragmentation allows one to predict the chemical structure of the nascent macromolecular layers.…”
Section: Resultsmentioning
confidence: 99%
“…The results presented above show that plasmas using vapours from the alcohol family are capable of improving adhesion of a:SiO x C y H z coating on polycarbonate if sufficiently long enough treatment times are used. Previous studies of alcohol plasmas have focused on surface functionalisation34, 35 rather than adhesion. Kitova et al36, 37 reported the effect of an RF excited plasma of ethanol and argon on adhesion of a SiO 2 film on polycarbonate and PMMA.…”
Section: Discussionmentioning
confidence: 99%